Behavioral Biases and Investment Decision of Gen Z: The Role of Long-Term Orientation - Pricilia, Viona; Susilawaty, Lilis (MEC-J (Management and Economics Journal), 2025)
While the number of stock investors in Indonesia has been growing, many particularly from Generation Z, who currently lead the market, continue to exhibit non-rational tendencies when making investment choices. These tendencies are frequently shaped by cognitive distortions such as representative, availability, and herding biases. This research investigates how these biases impact Gen Z’s stock investment decisions and explores whether long-term orientation moderates these effects. The research gathered responses from 349 Indonesian Generation Z participants through an online survey, with the data subsequently examined using the PLS-SEM method. The results show that representative bias, availability bias, and herding bias significantly influence investment decision making. Long-term orientation significantly moderates the effect of herding bias but does not significantly moderate the effect of representative bias or availability bias. This study encourages Generation Z investors to recognize the impact of behavioral biases and the importance of long-term thinking. It also suggests that regulators and market institutions develop educational programs to help reduce bias-driven decisions among young investors.